Analysis of Maternal Risk Factors for Low-Birth-Weight Infants at the Public Health Center - Fitri Handayani; Indasah Indasah; Yenny Puspitasari (Indonesian Journal of Global Health Research, 2025)
Infants weighing less than 2500 grams are classified as low birth weight (LBW) and have a high mortality rate in the first few days of life, as well as various complications over time. It is necessary to identify maternal risk factors that influence this condition so that it can be prevented early on. Objective: This study aimed to analyze the influence of maternal age, antenatal care (ANC) visits, anemia, smoking history, infectious diseases, and psychosocial factors on the occurrence of low birth weight in Kotawaringin Barat District Health Centers. Method: This inferential study used a retrospective observational design and was conducted from August to October at Semanggang Health Center. The study analyzed data from medical records and relevant documents collected between January and October 2024, involving 242 respondents. Data processing included organization, cleaning, and coding to ensure accuracy. Regression analysis was conducted to examine relationships between independent and dependent variables, supported by descriptive statistics to summarize respondent characteristics. Results: The results showed that maternal factors that positively contributed to preventing LBW were ANC visits (increasing birth weight by 134,421 times), Hb levels above 10 gr% (increasing birth weight by 65,506 times), and maternal age (increasing birth weight by 2,243 times) from 1500 grams, assuming other variables were constant. Meanwhile, maternal factors that negatively contributed to preventing LBW were infectious diseases (decreasing birth weight by 382,863 times), psychosocial factors (decreasing birth weight by 18,778 times), and smoking (decreasing birth weight by 5,064 times) from 1500 grams, assuming other variables were constant. Conclusions: In conclusion Adequate ANC visits, Hb levels above 10 gr%, and optimal maternal age significantly increase birth weight. Conversely, infections, psychosocial factors, and smoking increase the risk of low birth weight.